Prion protein preamyloid and amyloid deposits in Gerstmann-Sträussler-Scheinker disease, Indiana kindred. - Giaccone, G (1992)
Gerstmann-Sträussler-Scheinker disease (GSS) is a familial neurological disorder pathologically characterized by amyloid deposition in the cerebrum and cerebellum. In GSS, the amyloid is immunoreactive to antisera raised against the prion protein (PrP) 27-30, a proteinase K-resistant peptide of 27-30 kDa that is derived by limited proteolysis from an abnormal isoform of a neuronal sialoglycoprotein of 33-35 kDa designated PrPSc. Polyclonal antibodies raised against synthetic peptides homologous to residues 15-40 (P2), 90-102 (P1), and 220-232 (P3) of the amino acid sequence deduced from hamster PrP cDNA were used to investigate immunohistochemically the distribution of PrP and PrP fragments in the brains of two patients from the Indiana kindred of GSS. Two types of anti-PrP-immunoreactive deposits were found: (i) amyloid deposits, which were exclusively labeled by anti-P1 antiserum to residues 90-102 of PrP, and (ii) preamyloid deposits, which were labeled by all anti-PrP antisera but did not exhibit the tinctorial and optical properties of amyloid. The latter appeared as diffuse immunostaining of the neuropil that targeted to areas in which amyloid deposits were most abundant. They were partially resistant to proteinase K digestion and consisted ultrastructurally of amorphous, flaky, electron-dense material. These findings substantiate our previous observation that the major amyloid component in the GSS Indiana kindred is an internal fragment of PrP and indicate that full-length abnormal isoforms of PrP and/or large PrP fragments accumulate in brain regions most affected by amyloid deposition. These findings support the view that in the GSS Indiana kindred a stepwise degradation of PrP occurs in situ in the process of amyloid fibril formation.